The features of the organization of providing free legal aid system by non-state actors - Strukova, Kristina (Actual problems of law (Aktual’ni problemi pravoznavstva), 2018)
In the article administrative-normative nature, legal nature, role and place of the system of centers of free legal aid system of rights and freedoms of citizens, given the complex characteristics of the state and social institutions that should ensure the implementation of the right